Identifikasi Kualitatif Ekstrak, Fraksi n-Heksan, Fraksi Etil Asetat, Fraksi Air Herba Bandotan (Ageratum conyzoides L.) - Ayu Palupi, Dwi; Pratimasari, Diah; C.E. Dhurhania (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2025)
Bandotan (Ageratum conyzoides L.) is a plant that grows in subtropical and tropical regions and has high growth and adaptability. Some studies have shown that Bandotan herb has good activity as an antibacterial, anti-inflammatory, antioxidant, and antidiabetic agent. Existing research is limited to the content and activity of Bandotan herb extracts. However, some extracts that undergo fractionation are known to enhance their activity. Therefore, this study aims to identify the flavonoid and phenolic compounds in the polar, semi-polar, and non-polar fractions of Bandotan herb. The research started with macerating the Bandotan herb using ethanol as a solvent and concentrating it to obtain a thick extract. This thick extract was then suspended in warm water and fractionated successively using n-hexane and ethyl acetate solvents. The extracts and fractions obtained were analyzed for their content using tube tests and Thin Layer Chromatography (TLC). The tube test results indicated that the extract, ethyl acetate fraction, and water fraction were positive for flavonoids, while the n-hexane fraction was negative for flavonoids. TLC results showed variations in the compound profiles among the extract and its different fractions.